Corneal epithelial thickness analysis of forme fruste keratoconus with optical coherence tomography - Xiao-Long Yang; Yun Wang; Bao-Gen Luo; Yue Xu; Xiao-Feng Zhang (International Journal of Ophthalmology, 2021)
AIM: To explore the significance of corneal epithelial thickness analysis in diagnosing early keratoconus. METHODS: There were 26 clinical keratoconus, 21 forme fruste keratoconus, 40 high corneal astigmatism (ΔK) and 40 low ΔK eyes involved in the study. Fourier-domain optical coherence tomography was used to measure the corneal epithelial thickness of four groups. The morphological features of topographic map and the thickness of corneal epithelial thinnest point were analyzed. The distribution curve of corneal epithelial thickness at 45°, 90°, and 135° axial directions that are through the pupil center was also analyzed. One-way ANOVA was performed to compare the data. RESULTS: The topographic map of forme fruste keratoconus corneal epithelial thickness was uniformity shape; crater shape existed only in clinical keratoconus group; and central island shape mainly existed in high ΔK group. The thinnest point of corneal epithelial thickness of forme fruste keratoconus group was significantly lower than that of low ΔK group (P=0.022). The thickness of corneal epithelium in the forme fruste keratoconus at 90° was thinner than that in the low astigmatism group at -1, and -2 mm points (P-1 mm=0.015, P-2 mm=0.036). CONCLUSION: The analysis of the thinnest point in forme fruste keratoconus corneal epithelium appears earlier than corneal epithelial remodeling. The topographic map of corneal epithelium in high ΔK eyes appears in central island shape, and can be used for the differential diagnosis of early keratoconus.